Study on the Improvement of Corrosion Resistance of Mg-Gd-Y Alloys through Chemical Vapor Deposition of Cr/DLC films - HE Mingge, LIU Wenbo, YANG Liuqing, HE Qiuyun, ZHANG Mingyou, YUAN Yiqi, YANG Chuanqin, HE Bo (Cailiao Baohu)
Mg-Gd-Y alloys， as an excellent engineering material， have extensive applications in the exploration and development of petroleum and natural gas.In order to improve the corrosion resistance of Mg-Gd-Y alloy in underground service， the effect of diamond-like carbon(DLC) with Cr as a transition layer on the corrosion resistance of the Mg-Gd-Y alloy was investigated.The diamond-like carbon film with Cr as the transition layer was prepared using the PECVD method.The carbon structure type of the DLC film layer was analyzed using Raman spectroscopy.The corrosion resistance of the sample was evaluated through 3.5%(mass fraction) NaCl salt spray corrosion test， electrochemical polarization test， and contact angle test.The surface morphology and cross-sectional morphology of the sample before and after corrosion were analyzed using scanning electron microscopy (SEM).Results showed that the ID/IG value of the Cr/DLC film was 0.64， calculated from the Raman spectroscopy data， indicating that the sp3 hybridized bonds in the film layer were found to account for a larger proportion and that the structure was dense； therefore， the corrosion tendency and corrosion rate of the Cr/DLC film in 3.5%NaCl solution decreased.The corrosion resistance of the magnesium alloy substrate was effectively improved by the Cr/DLC film.